A high-precision 1 × 15 infrared temperature measurement linear array based on thermopile sensors - Bai, Jindong; Yang, Wenhang; Zhu, Shouzheng; Jin, Haijun; Zhang, Yuchen; Jin, Ke; Liu, Xiaoshuai; Li, Chunlai; Wang, Jianyu; Qi, Hongxing; Liu, Shijie (Communications engineering, 2025)
In applications such as those in the semiconductor industry, precise temperature measurements with low power consumption are crucial. This article presents a novel noncontact temperature measurement method with low power consumption and high precision, and a thermopile sensor-based linear array for surface temperature measurements is used in semiconductor manufacturing and temperature calibration applications. The array consists of 15 thermopile sensors, a negative temperature coefficient (NTC) thermistor, an FPGA control board with a fiber optic interface, and a motion module. Moreover, the total power consumption of the board is less than 1.5 W. On the FPGA control board, a multiparameter temperature compensation algorithm is used to address intrinsic temperature differences and consistency errors among the sensors. Compared with the traditional two-point calibration method, the temperature measurement accuracy of the proposed method reaches 26 mK in the temperature range of 293–303 K, the maximum repeatability error of the sensor is less than 5.5 mK, and the non-uniformity error between 15 sensors is less than 11.9 mK. The array and its replicas were subjected to more than 6 h of rigorous testing, demonstrating their high stability, with the reduction in accuracy not exceeding 1.5 mK. Non-contact infrared thermometry with high precision and low power consumption is critical for semiconductor manufacturing. Jindong Bai, Wenhang Yang, and colleagues, present a 15-sensor thermopile array using multiparameter compensation, achieving 25 mK accuracy, >2 W power, and 15.9 mK sensor consistency, enabling reliable thermal monitoring in industrial applications.